Don’t neglect the non-thrombotic manifestations of antiphospholipid syndrome in children – autoimmune hemolytic anemia and myocarditis: a case report and literature review - Cui, Wanlin; Sun, Yuming; Zhao, Danyang; Varkani, Masumeh Nozzari; Wang, Guan; Wen, Xiaoqing; Shi, Mingyue; Wang, Xiaohan; Zhang, Xinyi; Jiang, Hongkun (Frontiers in Immunology, 2026)
Antiphospholipid Syndrome (APS) is a systemic autoimmune disorder characterized by persistent antiphospholipid antibodies, associated with thrombosis or adverse pregnancy outcomes. Although non-thrombotic manifestations are less common than thrombotic events, they play an increasingly important role in diagnosis and disease progression, particularly in pediatric APS, and may interact with each other. Early recognition and management of these symptoms are crucial for patient prognosis. We present a case of 13-year-old male child presenting as autoimmune hemolytic anemia (AIHA) and myocarditis, with positive antiphospholipid antibodies (aPL). The patient showed significant improvement after combination therapy with corticosteroids, prophylactic low molecular weight heparin and aspirin. In addition, we conducted a comprehensive literature review on APS in conjunction with hemolytic anemia and cardiac complications, and found that in 171 APS cases with hemolytic anemia, 35 of them had cardiac complications. There were 8 cases of myocardial infarction (8/171,4.7%) and 3 cases of myocarditis (3/171, 1.8%). Compared with AIHA, the incidence of cardiopathy was significantly higher in microvascular hemolytic anemia (MAHA) (p = 0.020). Among 13 cases that recorded the time window from hemolytic anemia to cardiac symptoms, 92.3% of them developed cardiac complications within one year after the onset of hemolytic anemia, typically within a median interval of 3 months (ranging from 5 days to 2 years). Notably, 28.6% of the 35 cases reviewed involved children under 18, with nearly half presenting hemolytic anemia as the initial symptom. This case underscores APS patients with hemolytic anemia, particularly MAHA, require early intervention and timely cardiac follow-up. Given the current lack of definitive classification and treatment criteria for pediatric APS, future guidelines should incorporate the significance of non-thrombotic manifestations and emphasize early management strategies.